Accidental hypothermia in Denmark: A nationwide cohort study of incidence and outcomes. Issue 5 (31st May 2021) - Wiberg, Sebastian; Mortensen, Asmus Friborg; Kjaergaard, Jesper; Hassager, Christian; Wanscher, Michael
Abstract : Objectives: To investigate the incidence of accidental hypothermia (AH) in a nationwide registry and the associated outcomes. Design: Nationwide retrospective cohort study Participants and settings: All patients at least 18 years old, admitted to hospitals in Denmark with a diagnosis of AH, with an International Classification of Diseases, 10th edition code of T689, from January 1996 to November 2016. Other recorded diagnoses were included in the analyses. Primary and secondary outcome measures: The primary outcome was 1-year mortality. Results: During the inclusion period, 5242 patients were admitted with a diagnosis of AH, corresponding to a mean annual incidence of 4.4±1.2 (range by calendar year: 2.9–6.4) per 100 000 inhabitants. A total of 2230 (43%) had AH recorded as the primary diagnosis without any recorded secondary diagnoses (primary AH), 1336 (25%) had AH recorded as the primary diagnosis with other recorded secondary diagnoses (AH+2° diagnosis), and 1676 (32%) had AH recorded as a secondary diagnosis with another recorded primary diagnosis (1° diagnosis+AH). Alcohol intoxication was the most common diagnosis associated with AH. Overall 1-year mortality was 27%. In patients with primary AH, 1-year mortality was 22%, compared with 26% in patients with secondary AH type I, and 35% in patients with secondary AH type II (plog-rank <0.001). Conclusions: The present study investigated the incidence of AH, associated comorbidities and mortality after AH in Denmark from 1995 to 2016. The diagnosis is associated with a high comorbidity burden and a considerable 1-year mortality. In the high proportion of patients with associated comorbidities, establishing whether AH or the comorbidities are the drivers of mortality remains difficult. This complicates our understanding of AH and makes it difficult to find modifiable factors associated with both AH and outcomes. Future prospective studies are needed elucidate the causal relationship between AH and associated comorbidities.